The Effect of Umkm on Improving Community Welfare in Disadvantaged Areas - Anisa, Karolina; Hastro, Boy (Yayasan Cinta Negara Indonesia, 2025)
This study examines the influence of Micro, Small, and Medium Enterprises (UMKM) on improving community welfare in underdeveloped regions. UMKM plays a crucial role in fostering local economic growth by providing employment opportunities, increasing household incomes, and reducing poverty in these areas. This research explores the contribution of UMKM to local socio-economic development, focusing on their role in creating jobs, enhancing education through skill development, and facilitating social mobility. Furthermore, the study investigates the challenges faced by UMKM, including limited access to financing, technology, and markets, which hinder their growth and sustainability. The findings highlight the importance of supportive government policies, infrastructure development, and capacity-building programs in overcoming these barriers. The study concludes that UMKM is a vital driver of economic and social transformation in underdeveloped regions, contributing significantly to the improvement of community welfare. The research provides practical recommendations for policymakers, financial institutions, and other stakeholders to strengthen UMKM’s role in driving sustainable development in these areas